INVESTIGASI KEWIRAUSAHAAN SEBAGAI VARIABEL MODERASI KEPUTUSAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN - Erna Setijani; Pudjo Sugito; Chodidjah Chodidjah (Jurnal Keuangan dan Perbankan, 2015)
This study intends to analyze the role of entrepreneurship as a moderating variable on the effects of capitalstructure decisions on financial performance. Population, all the small and medium industries (SMEs) in thetown of Probolinggo, with a sample set of 100 units of SMEs and data collection using purposive randomsampling technique. Data were analyzed using factor analysis in the SEM is used to confirm the most dominantfactors in a group of variables and regression weight on the SEM used for confirmatory examine howmuch the relationship between variables. Furthermore, SEM modeling needs to step (a) the development of atheoretical model, (b) the development path diagram (c) selecting an input matrix and estimation of covarianceor correlation models, (d) the possibility of the emergence of problem identification, (e) evaluation criteria ofgoodness-of-fit and (f) the interpretation and modification of the model. The results showed, capital structuredecisions have a significant effect on financial performance. Capital structure decisions have a significanteffect on the financial performance through entrepreneurship moderating variable. Entrepreneurship significanteffect on the financial performance.